PHOTOSYNTHETIC PRODUCTIVITY OF SOYBEAN DEPENDING ON SOWING TIME AND METHOD OF APPLICATION OF MICROFERTILIZERS - Шовкова, О. В. (Scientific Progress & Innovations, 2014)
Photosynthesizing activity of crops, including soybeans, is the main component of the formation of their productivity. Optimal growth of the leaf surface and dry matter accumulation of soybean plants largely depends on the validity of cultivation technologies that ensure long-term operation leaf apparatus. Seed treatment with microfertilizer chelate based on "Rexolin" and foliar feeding with "Rexolin" and "Brasitrel" on different dates of sowing soybean crops intensified photosynthetic activity of a given culture. Integrated application of microfertilizers to seed and vegetative plants promoted the formation of the maximum performance of the leaf surface and pure photosynthetic productivity.